Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.3102/00028312024004611
|View full text |Cite
|
Sign up to set email alerts
|

Instruction Addressing the Components of Scientific Literacy and Its Relation to Student Outcomes

Abstract: The instruction of 11 seventh-grade life science teachers was observed to determine the extent to which they made linkages between science content and its societal, reasoning, historical, or attitudinal implications. Such linkages were hypothesized to facilitate students’ scientific literacy. Data on students’ perceptions of teacher instruction and scientific literacy outcomes were also gathered. Results showed that (a) teachers rarely or never addressed the noncontent components of science in their presentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

1988
1988
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 6 publications
1
4
0
2
Order By: Relevance
“…The Mitman et al (1987) study also reported that teachers who spent more time making content references that were enriched with references to loftier objectives had significantly lower student gains in scientific reasoning than teachers who merely "covered" the content. Examination of specific instructional procedures indicated that the unexpected finding could be attributed to the weakness of the techniques used.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The Mitman et al (1987) study also reported that teachers who spent more time making content references that were enriched with references to loftier objectives had significantly lower student gains in scientific reasoning than teachers who merely "covered" the content. Examination of specific instructional procedures indicated that the unexpected finding could be attributed to the weakness of the techniques used.…”
Section: Discussionmentioning
confidence: 92%
“…Brandwein (1981) found that experiments undertaken by American students merely documented what teacher and text had described. Mitman, Mergendoller, Marchman, and Packer (1987) found that almost all teacher talks and student assignments focused on content acquisition; attention to the reasoning processes in science was extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…Research has repeatedly documented that students who demonstrate successful learning of a scientific principle or concept on a daily assignment often fail to use it to solve problems on another occasion (Bransford et al, 1986(Bransford et al, , 1989(Bransford et al, , 1991Reys et al, 1982;Schoenfeld, 1987;Smith & Good, 1984;Whitehead, 1929). Students often revert to inappropriate pre-instructional conceptual frameworks in real life problem solving (Mitman et al, 1987;Tobin et al, 1988).…”
Section: Science Contentmentioning
confidence: 99%
“…Cela dit -et malgré l'appui de conseillers pédagogiques crédibles (Shrigley, 1980;Perrine, 1984) et de manuels scolaires généralement adéquats (Meyer, Crummey et Gréer, 1988)--, l'enseignant doit assumer la responsabilité ultime de cet enseignement renouvelé des sciences. Il arrive souvent qu'il soit désarmé devant cette tâche au point qu'il se rabat sur des stratégies d'enseignement qui révèlent une conception plus traditionnelle des sciences, conception qui les réduit à une simple accumulation de connaissances (Oison et Reid, 1982;Mitman, Mergendoller, Marchman et Packer, 1987).…”
Section: Programmes D'enseignement Et Leur Implicationunclassified